Ethical Issues in Developing Pharmacogenetic Research Partnerships American Indigenous Communities - Boyer, Bert B. (2011)
Pharmacogenetic research offers the potential to improve the safety and efficacy of drug prescribing. Assuring that the benefits of this research reach indigenous and other medically underserved people is an important justice concern. First, however, a legacy of mistrust, derived from traditional research practices that disempower communities, must be overcome. Linking pharmacogenetic research to collaborative, power-sharing research partnerships provides a valuable opportunity to develop new and positive precedents for genetic research in indigenous communities.